Lymphoproliferative Lesions in the Setting of HIV Infection: A Five-Year Retrospective Case Series and Review. (22nd February 2011) - Mahe, Etienne; Ross, Catherine; Sur, Monalisa
Abstract : A wide variety of noninfectious lesions have been identified in association with HIV infection. Many hematolymphoid lesions are possible in this patient group, both reactive and neoplastic. Epidemiologic data suggests that lymphoid malignancies are among the most common neoplasms in patients with HIV. We present a selective case series assembled over a 5-year period from the relatively low HIV-prevalence Hamilton Regional Laboratory Medicine Program (HRLMP), a tertiary care referral centre in Southern Ontario. This series serves to demonstrate the wide variety of lymphoid lesions that may be encountered in patients with HIV. In addition to outlining the pathologic work-up necessary in these cases, we discuss characteristics that distinguish the HIV-associated lesions from the pathobiologically similar non-HIV-associated lymphoid lesions.